Reading Corner as a Medium for Increasing Interest in Reading in Tenrigangkae Village - Muh. Rezky Budi Santoso; Muhammad Ammar Naufal; Zaid Zainal (Journal of Community Services and Development, 2025)
The reading interest of Indonesians is still relatively low, especially in rural areas. A similar condition was found in Tenrigangkae Village, where children spend more time with their gadgets than reading books. To address this issue, a reading corner program was designed as an alternative means of improving basic literacy by providing a simple, comfortable, and child-friendly reading space. This study used a qualitative descriptive method with a field research approach, through the stages of preparation, implementation, and evaluation. Data were collected through observation, interviews, and documentation. The results show that the reading corner, which was rearranged with a diverse collection of reading materials, simple decorations, and supported by joint literacy activities, was able to attract children's enthusiasm for reading. The evaluation showed positive behavioral changes, namely an increase in interest, involvement, and reading habits. These findings confirm that reading corners not only function as book storage spaces but also as effective educational tools in fostering a culture of literacy in rural areas. Prospects for developing this program include adding to the reading collection, organizing ongoing literacy activities, and involving teachers and parents so that it can be replicated as a model for community-based literacy empowerment